Sustaining Local Industry: Linkages Between SME And Hotel Industries In Labuan Bajo - Reynaldo Angga Siagian; Yohanes Paulus Hanny Wadhi; Katarina Noviming Sakura; Togar Wiliater Soaloon Panjaitan (JURNAL AKADEMISI VOKASI, 2023)
Tourism has become an economic sector that contributes to the country. Labuan Bajo is currently one of the primadonna of new tourism in Indonesia where the main focus of consumers is foreign tourists. With the development of tourism like that, tourism seems to provide small benefit to the local community. Therefore, the current focus is how to build a relationship between tourism and local industry. This study analyzes the proportion of purchasing hotel products from MSMEs and also the economic opportunities available to MSMEs in the hotel industry in Labuan Bajo. The data is obtained from a survey conducted at 12 hotels to find out what opportunities have the most potential to be able to form cooperation between MSMEs and the hotel sector. From the analysis, it was found that the most potential cooperation is in the field of waste transportation, food supply, souvenirs as well as services related to maintenance and repair. This can have implications for the role of tourism to the growth of the local industry followed by an increase in the economy in the local community.